(untitled) (Research, Society and Development, 2020)
This article aims to analyze the management philosophy based on Strategic Business Units (SBU), pointing its origin and confronting the ideas of its main authors. Given the literary scarcity of the subject, the text develops through exploratory research. As a result, General Electric’s case will be exposed and commented on, analyzing the difficulties faced by the group in the 60s and pondering how these issues enabled the development of the SBU-based management platform. It then recovers the literature and develops a synoptic reading of the works cited, emphasizing relevant issues that have not yet been developed by science. In conclusion, it is pointed out how this philosophy can contribute to the achievement of perpetuity in modern organizations.